Promoting walking among office employees - evaluation of a randomized controlled intervention with pedometers and e-mail messages - Aittasalo Minna; Rinne Marjo; Pasanen Matti; Kukkonen-Harjula Katriina; Vasankari Tommi (BMC, 2012)
Abstract Background The purpose of the study was to evaluate a 6-month intervention to promote office-employees' walking with pedometers and e-mail messages. Methods Participants were recruited by 10 occupational health care units (OHC) from 20 worksites with 2,230 employees. Voluntary and insufficiently physically active employees (N = 241) were randomized to a pedometer (STEP, N = 123) and a comparison group (COMP, N = 118). STEP included one group meeting, log-monitored pedometer-use and six e-mail messages from OHC. COMP participated in data collection. Reach, effectiveness, adoption, implementation, maintenance (RE-AIM) and costs were assessed with questionnaires (0, 2, 6, 12 months), process evaluation and interviews (12 months). Results The intervention reached 29% (N = 646) of employees in terms of participation willingness. Logistic regression showed that the proportion of walkers tended to increase more in STEP than in COMP at 2 months in "walking for transportation" (Odds ratio 2.12, 95%CI 0.94 to 4.81) and at 6 months in "walking for leisure" (1.86, 95%CI 0.94 to 3.69). Linear model revealed a modest increase in the mean duration of "walking stairs" at 2 and 6 months (Geometric mean ratio 1.26, 95%CI 0.98 to 1.61; 1.27, 0.98 to 1.64). Adoption and implementation succeeded as intended. At 12 months, some traces of the intervention were sustained in 15 worksites, and a slightly higher number of walkers in STEP in comparison with COMP was observed in "walking stairs" (OR 2.24, 95%CI 0.94 to 5.31) and in "walking for leisure" (2.07, 95%CI 0.99 to 4.34). The direct costs of the intervention were 43 Euros per participant. Conclusions The findings indicate only modest impact on some indicators of walking. Future studies should invest in reaching the employees, minimizing attrition rate and using objective walking assessment. Trial registeration ISRCTN79432107